A unique miracle: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story highlights a miraculous event that showcases divine intervention in the lives of believers, inspiring faith and hope. It emphasizes the extraordinary power of faith in overcoming challenges.